Urbana utväxter : konsumtionskoncentrat - Fahlsten, Sara (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The shopping mall is a reflection of the city and its habitants, a concentrate of the modern city. I have studied the dialogues of malls and the communication within, how malls are put together and what they communicate.